The Penta Helix Synergy in Creating DESA BESTARI a Smart Village Marvel - Dida Nurhaida; Ida Busnetty; Tulus Tulus Tahi Hamonangan Tambunan; Nurlida Fatmikasari; Ardiyanto Ardiyanto (Universitas Negeri Semarang, 2024)
Rural communities encounter distinct development challenges, necessitating innovative solutions like the smart village initiative. This article delves into the successful implementation of the